Sankcje w postaci kar pieniężnych - Wierzbowski, Marek; Żywicka, Agnieszka (Studia Prawa Publicznego, 2023)
Over the several decades of her scientific activity, Professor Teresa Rabska played an outstanding role in the formation of Polish administrative law, particularly during the political and economic transformations of the late 1980s, when Prof. Rabska was actively involved in the field. Within public economic law, the role of the state and its tools for influencing the economy have evolved fundamentally. In this area, the administrative sanctions with which administrative bodies were equipped have developed profoundly and taken on an important function. Undoubtedly, the European Union plays a significant role in the development of administrative penalties. Penalties are imposed in the form of administrative decisions, issued according to procedures governed by the Code of Administrative Procedure. This Code and other laws enumerate the prerequisites for assessing a penalty. Among these, the omission of the element of guilt must be a cause for concern. Consequently, particularly in the case of penalties imposed on individuals, the penalty may be imposed on a person to whom no fault can be attributed in the violation of the law that caused the punishment. The system of fines thus arouses great dissatisfaction among market participants. An analysis of the system of administrative penalties in Poland raises the issue of harmonizing solutions on the scale of the European Union, as it is expected that penalties should be of similar size in all member states. However, the statutory enshrinement of high penalties in the current legislation does not prejudge the practice of imposing them. Given the smaller revenues generated in Poland, the penalties imposed should be proportionately lower. Moreover, the law does not categorically require the imposition of high penalties. The legislation often uses the word “may,” from which some people draw conclusions about the imposition of penalties under administrative discretion, which is not legitimate.